Determining Subclinical Cardiovascular and Cardiac Diseases in Patients with Non-Alcoholic Fatty Liver Disease - Karaoğlan, Beliz Bahar; Tulunay, Cansın; Uzun, Çağlar; Peker, Elif; Özyüncü, Nil; Ellik, Zeynep; Kuru, Diğdem; Turhan, Sibel; Savaş, Berna; Erden, Ayşe; et al. (Turkish Journal of Gastroenterology, 2022)
Background: The aims of the present study were to determine the subclinical coronary atherosclerosis and myocardial dysfunction in patients with non-alcoholic fatty liver disease (NAFLD), who were asymptomatic for cardiac disease. Methods: A total of 61 non-alcoholic fatty liver disease patients were enrolled in the study. The 10-year probability of cardiovascular events was evaluated according to the pooled cohort equation risk score (atherosclerotic cardiovascular disease). The coronary artery calcium score was measured. Conventional echocardiographic examination was followed by 2- and 3-dimensional speckle tracking echocardiography. Results: Patients with non-alcoholic steatohepatitis had significantly higher insulin resistance (P = .018), serum alanine aminotransferase (P = .002) and aspartate aminotransferase levels (P = .021), hepatic steatosis (P = .023), and fibrosis (P = .001) than non-alcoholic fatty liver disease patients. The mean Atherosclerotic Cardiovascular Disease score was 7.5% ± 6.9% and 37% of the patients had medium and high cardiovascular disease risk. Cardiovascular disease (>1) was found in 30% of the patients. Interestingly, 56% had significant and extended atherosclerotic plaques. Among the patients with moderate-to-high atherosclerotic cardiovascular disease scores, 63% had significant atherosclerotic plaques and 21% had extensive plaque burden. The presence of non-alcoholic steatohepatitis did not significantly affect cardiovascular risk. Non-alcoholic steatohepatitis was deleterious on left ventricle diastolic functions. Mean A velocity in non-alcoholic steatohepatitis patients was significantly increased compared to non-alcoholic fatty liver disease patients (87.0 ± 17.5 cm/s vs. 72.3 ± 13.6 cm/s, P = .002). Mean E/e’ ratio was 8.1 ± 2.0. Submyocardial fibrosis detected had a slightly higher occurrence in non-alcoholic steatohepatitis patients than in non-alcoholic fatty liver disease patients (P = .530). Conclusion: NAFLD seems to be associated with an increased risk of subclinical cardiovascular disease and myocardial dysfunction in asymptomatic patients with cardiac disease. Cite this article as: Karaoğlan BB, Tulunay C, Uzun Ç, et al. Determining subclinical cardiovascular and cardiac diseases in patients with non-alcoholic fatty liver disease. Turk J Gastroenterol. 2023;34(3):242-253.